2023
DOI: 10.1177/10963480231188001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Food Waste at a Hospitality Staff Canteen With Meteorological Data

Soey Sut Ieng Lei,
Elizabeth Agyeiwaah,
Lawrence Hoc Nang Fong
et al.

Abstract: While food waste in the hospitality industry remains a major global issue, the food waste practices of employees have been largely neglected. This paper explores the effects of meteorological factors on unserved food from the perspective of hospitality employees. A mixed methods research design is adopted with quantitative data obtained from the unserved food records of an integrated resort (IR) with additional meteorological data from an official government website. This quantitative data is complemented by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…The study revealed a negative effect, suggesting that a lack of alignment between hotels and OTAs hinders consumers' willingness to pay more for environmentally friendly accommodations. Lei et al (2023) examined the relationship between meteorological data and food waste at a hospitality staff canteen. The authors discovered that temperature and air pollutants such as sulfur dioxide and ozone influence the amount of food waste generated, highlighting the importance of environmental factors in waste management.…”
mentioning
confidence: 99%
“…The study revealed a negative effect, suggesting that a lack of alignment between hotels and OTAs hinders consumers' willingness to pay more for environmentally friendly accommodations. Lei et al (2023) examined the relationship between meteorological data and food waste at a hospitality staff canteen. The authors discovered that temperature and air pollutants such as sulfur dioxide and ozone influence the amount of food waste generated, highlighting the importance of environmental factors in waste management.…”
mentioning
confidence: 99%